2017
DOI: 10.1149/2.0231706jes
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Fluoroethylene Carbonate Additive in LiNi0.5Mn1.5O4- Li4Ti5O12Lithium-Ion Cells

Abstract: The effect of the electrolyte additive fluoroethylene carbonate (FEC) for Li-ion batteries has been widely discussed in literature in recent years. Here, the additive is studied for the high-voltage cathode LiNi 0.5 Mn 1.5 O 4 (LNMO) coupled to Li 4 Ti 5 O 12 (LTO) to specifically study its effect on the cathode side. Electrochemical performance of full cells prepared by using a standard electrolyte (LP40) with different concentrations of FEC (0, 1 and 5 wt%) were compared and the surface of cycled positive el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 29 publications
6
41
0
Order By: Relevance
“…Although the electrolytes showed high cycling stability of the Li-metal electrode, side reaction of FEC at the LCO cathode may cause the lower initial discharge capacities. 41 To verify the FEC decomposition and consequent LCO passivation for the electrolytes with high FEC contents, we also conducted a three-electrode impedance analysis for the Li/LCO cells with the control and 70FEC/30DEC electrolytes. As shown in Figure S6a, the cathode impedances for the control and 70FEC/30DEC electrolytes in the fully charged state after the first cycle exhibited two semicircles; the high frequency (500 Hz) and low frequency (5 Hz) semicircles are associated with Li + ion migration through a CEI film and with the charge-transfer process, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the electrolytes showed high cycling stability of the Li-metal electrode, side reaction of FEC at the LCO cathode may cause the lower initial discharge capacities. 41 To verify the FEC decomposition and consequent LCO passivation for the electrolytes with high FEC contents, we also conducted a three-electrode impedance analysis for the Li/LCO cells with the control and 70FEC/30DEC electrolytes. As shown in Figure S6a, the cathode impedances for the control and 70FEC/30DEC electrolytes in the fully charged state after the first cycle exhibited two semicircles; the high frequency (500 Hz) and low frequency (5 Hz) semicircles are associated with Li + ion migration through a CEI film and with the charge-transfer process, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The measurements shown here were carried out with ordered LNMO and Whatman® separators. Aktekin et al and Xiang et al showed longer cycle stability with disordered LTO/LNMO full cells with Celgard® separators [28,29]. However, the performance of the cells is not priority in this article but the mechanism of the degradation.…”
Section: Full Cellsmentioning
confidence: 95%
“…Different families of additives had proven their ability to improve the electrochemical performances of LNMO based cells. [18][19][20][21][22][23][24] Tu et al [19] found that trimethylsilyl cyclopentadiene as a novel electrolyte additive afforded a protection layer on LiNi 0.5 Mn 1.5 O 4 electrode surface, inhibiting additional electrolyte decomposition and transition metal dissolution for high temperature application of LiNi 0.5 Mn 1.5 O 4 . Xu et al [23] reported that addition of 0.5 wt% tri (pentafluorophenyl) phosphine (TPFPP) to the baseline electrolyte increased the capacity retention from 70.3 % to 85.0 % of its initial capacity for LiNi 0.5 Mn 1.5 O 4 after 55 cycles (0.2C).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, scientists were dedicated to searching for film‐forming additives that can be oxidized prior to the carbonate‐based electrolyte and formed a protective film to suppress further oxidative decomposition of the electrolyte and protect the active cathode from destruction at room and elevated temperature. Different families of additives had proven their ability to improve the electrochemical performances of LNMO based cells . Tu et al .…”
Section: Introductionmentioning
confidence: 99%